Analisis Potensi Pencemaran Airtanah di Daerah Dok IV Kota Jayapura - Karapa, Enos; Medyati, Novita (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Groundwater contamination is a threat that can endanger human health. Therefore, correct information is needed on the sources of groundwater used by the community. Seeing the development of the community around the Dok IV area which is very rapid and the use of groundwater which is quite large, it is necessary to carry out an investigation regarding groundwater in this area. This groundwater investigation aims to describe the hydrogeological conditions, to determine the chemical elements that are the pollutant load in groundwater and to determine the potential for seawater intrusion. The research method used is the hydrogeological mapping method, namely analysis of recharge and recharge areas, analysis of hydraulic slopes and well geometry. The subsurface investigation uses the subsurface estimation method with Ground Penetrating Radar (GPR). For chemical investigations carried out by taking groundwater samples and analyzing them at the Jayapura regional health laboratory.The results found showed that there were several chemical elements that exceeded the quality standard values. TDS increased in wells 1 and 2, iron increased in well 4, fecal coli in well 1 and coliform in all wells. Based on empirical calculations, the water absorption in this place is 4,069,391.723 m3. The presence of seawater is at a depth of 30 m, so it has not had an intrusive effect on groundwater.